UAVs Protection and Countermeasures in a Complex Electromagnetic Environment. (13th July 2022) - Belousov, Anton O.; Zhechev, Yevgeniy S.; Chernikova, Evgeniya B.; Nosov, Alexander V.; Gazizov, Talgat R.
Abstract : The study considers the problem of ensuring electromagnetic compatibility of EMI-based functional destruction means with other radioelectronic equipment as part of a complex for countering unmanned aerial vehicles. To solve this problem, it is proposed to create a methodology that combines a set of diverse approaches and methods. This study focuses on the use of hollow and thin passive conductors, the use of a magnetodielectric in a reflection symmetric modal filter, the use of reflection symmetric structures for decomposing the train of ultrashort pulses (USP), and the use of a meander line as a protective means against USPs. The main results that are expected to be obtained using the proposed approaches and methods are outlined.